Correction to: The relationship between comorbidity medication adherence and health related quality of life among patients with cancer - Dana Drzayich Antol; Adrianne Waldman Casebeer; Raya Khoury; Todd Michael; Andrew Renda; Sari Hopson; Aparna Parikh; Alisha Stein; Mary Costantino; Stephen Stemkowski; Mikele Bunce (SpringerOpen, 2021)
An amendment to this paper has been published and can be accessed via the original article.